Tipificación en la legislación penal ecuatoriana de los delitos de incumplimiento de obligaciones, simulación, fraude y enriquecimiento injusto en materia laboral - Calderón Guzmán, Gabriela Lorena (2014)
The Labor Right as integral branch of the Social Right, it has sought to compare or to give a balance to the integrant parts of the labor relationship, especially to the proletarian and worker classfrom the acquaintances social fights for the maximum day of eight daily hours, for fair remunerations, and with a special focus to the constitutional process of the Ecuador that in the year 2008 by means of approbatory referendum, it promulgated by means of the Constituent Assembly the supreme norm of the Republic, starting of the elimination in the precarious ways of labor recruiting, and with a new consistent challenge in to penalize and to sanction some behaviors that continue affecting to the labor relationships. In this topic, the Constitution of the Republic of the Ecuador in their article 327 have established that the labor relationship will be direct and bilateral, being prohibited all outsourcing form, intermediation or labor precarious, and it has also prepared that the nonfulfillment of obligations, the fraud, the simulation and unjust enrichment in labor matter will be penalized and sanctioned in accordance with the law. The constitutional order is clear, it is necessary to penalize and to sanction the behaviors indicated in the previous paragraph, what bears to the necessity of making a juridical-doctrinal study for the legal typification of these behaviors that should have antijuristic when harming the labor rights that are unalienable, intangible and unavoidable. The Ecuadorian penal legislation, with the Penal Code that recently was repealed by the Code Organic Penal Integral, some typical behaviors that deserve sanction already settled down and that they have intimate relationship with the labor environment, such as: demand of services not imposed by the law or contract; work suspension for and it stops illicit ends; the employer coaction to force to participate in boycott or labor society; and, the impediment of the exercise of the petition right. With content essentially focused to the association rights, boycott or paralyzed work, suspension of the work and the right of the worker's petition. With the current Code Organic Penal Integral, the impediment behaviors or limitation have settled down from the right to strike; illegal retention of contributions to the social security and the affiliation lack to the Ecuadorian Institute of Social Security. Nevertheless the new one normative penal that will enter in validity starting from hundred eighty days from their publication in the Supplement of the Registration Official Number 180 of the day Monday February 10 the 2014, it doesn't regulate the figures of nonfulfillment of obligations, fraud, simulation and unjust enrichment in labor matter. Appearingof the necessity,the typification of such behaviors with the determination of the constituent circumstances and their respective penalization or sanction.